Targeted and non-targeted proteomics to characterize the parasite proteins of Echinococcus multilocularis metacestodes - Müller, Joachim; Preza, Matías; Kaethner, Marc; Rufener, Reto; Braga, Sophie; Uldry, Anne-Christine; Heller, Manfred; Lundström-Stadelmann, Britta (Frontiers in Cellular and Infection Microbiology, 2023)
The larval stage of the cestode Echinococcus multilocularis is the causative agent of alveolar echinococcosis. To investigate the biology of these stages and to test novel compounds, metacestode cultures represent a suitable in vitro model system. These metacestodes are vesicles surrounded by an envelope formed by the vesicle tissue (VT), which is formed by the laminated and germinal layer, and filled with vesicle fluid (VF). We analyzed the proteome of VF and VT by liquid chromatography tandem mass spectrometry (LC-MS/MS) and identified a total of 2954 parasite proteins. The most abundant protein in VT was the expressed conserved protein encoded by EmuJ_000412500, followed by the antigen B subunit AgB8/3a encoded by EmuJ_000381500 and Endophilin B1 (protein p29). In VF, the pattern was different and dominated by AgB subunits. The most abundant protein was the AgB8/3a subunit followed by three other AgB subunits. In total, the AgB subunits detected in VF represented 62.1 % of the parasite proteins. In culture media (CM), 63 E. multilocularis proteins were detected, of which AgB subunits made up for 93.7 % of the detected parasite proteins. All AgB subunits detected in VF (encoded by EmuJ_000381100–700, corresponding to AgB8/2, AgB8/1, AgB8/4, AgB8/3a, AgB8/3b and AgB8/3c) were also found in CM, except the subunit encoded by EmuJ_000381800 (AgB8/5) that was very rare in VF and not detected in CM. The relative abundance of the AgB subunits in VF and CM followed the same pattern. In VT, only the subunits EmuJ_000381500 (AgB8/3a) and EmuJ_000381200 (AgB8/1) were detected amongst the twenty most abundant proteins. To see whether this pattern was specific to VF from in vitro cultured metacestodes, we analyzed the proteome of VF from metacestodes grown in a mouse model. Here, the AgB subunits encoded by EmuJ_000381100 – 700 constituted the most abundant proteins, namely 81.9 % of total protein, with the same order of abundance as in vitro. Immunofluorescence on metacestodes showed that AgB is co-localized to calcareous corpuscles of E. multilocularis. Using targeted proteomics with HA-tagged EmuJ_000381200 (AgB8/1) and EmuJ_000381100 (AgB8/2), we could show that uptake of AgB subunits from CM into VF occurs within hours.